Lenalidomide in patients with chemotherapy‐induced polyneuropathy and relapsed or refractory multiple myeloma: results from a single‐centre prospective study. Issue 1 (22nd March 2013) - Briani, Chiara; Torre, Chiara Dalla; Campagnolo, Marta; Lucchetta, Marta; Berno, Tamara; Candiotto, Laura; Padua, Luca; Ermani, Mario; Cavaletti, Guido; Zambello, Renato
Abstract Lenalidomide, an immunomodulatory drug used in myeloma therapy, has been claimed to be less neurotoxic than thalidomide, but evidence is still weak. We prospectively assessed lenalidomide safety in myeloma patients to evaluate whether it would induce or modify a previously ensued chemotherapy‐induced peripheral neuropathy (CIPN). Thirty consecutive patients (17 men, mean age 63.7 ± 9.4) previously treated with bortezomib and/or thalidomide and starting on lenalidomide (25 mg/day for 21‐day cycles) for relapsed or refractory myeloma were assessed at baseline, 6, and 12 months from the beginning of lenalidomide with Total Neuropathy Score clinical version (TNSc), Eastern Cooperative Oncology Group (ECOG) performance status, and numeric rating scale (NRS) for pain. TNSc >2 was considered significant for CIPN. TNSc changes of at least 4 points from baseline value were considered clinically relevant. At baseline 16 of the 30 patients (53.3%) had CIPN (mean TNSc 5.8, range 3–15). After 6 months, 13 patients were unchanged, 1 improved, and 2 worsened. After 12 months the patient who had improved persisted stable, and the two who had worsened returned to TNSc baseline value. The 14 patients without CIPN at baseline did not develop neuropathy. NRS and ECOG performance status persisted unchanged. Our results demonstrate lenalidomide safety and very low neurotoxicity also in patients with pre‐existing CIPN treated for 1 year.